What are the Appropriate Leadership Styles for Class C Hospital in National Health Insurance (JKN) Era? - Kartikasari, Dhian; Manzilati, Asfi; Hariyanti, Tita (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
The form of leadership is able to determine the success of an organization including hospitals, so a leader needs to think about the right leadership style, especially in the JKN era. This study aims to explore the appropriate leadership style in X General Hospital so that it can get full accreditation and the hospital’s existence is still maintained until now. The study used a qualitative study design with a case study approach (case study) which was conducted at one of the Class C General Hospitals in Malang Regency which has collaborated with BPJS Kesehatan (Healthcare and Social Security Agency). The study involved employees who worked at General Hospital X and experienced hospital leadership during the JKN era during February-March 2020. Data collection techniques used three methods including interviews, observation, and document review. The results showed three major themes of leadership style including leadership style transformational, democratic leadership style, and moralist leadership style. The transformational leadership style is the core of the existence of General Hospital X in the JKN era, while the democratic and moral leadership style supports the existence of General Hospital X in the JKN era.